Effect of Modified Freezing Diluent on Post-Thaw Sperm Characteristics of Poor Freezable Sahiwal Bull - Sethi, Manisha; Shah, Nadeem; Mohanty, Tushar K; Bhakat, Mukesh; Yadav, Dileep K; Kumar, Pratyush; Kumar, Nishant (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study aimed to enhance the cryo-survivability and fertilization potential of poor freezable Sahiwal bull semen by devising a modified extender and freezing protocol. This protocol incorporated a combination of trehalose and glycerol as cryoprotectants and freezing with an aluminium block. The semen samples were split into three; the split 1 was extended in routine tris fructose egg yolk glycerol (TFEG) extender and underwent the conventional vapour freezing (Control group). The other split samples considered as treatment samples were extended with diluent having 75 % of TFEG and 25 % of trehalose (280 mOsm/l both) with glycerol percentage being 5, and frozen using a conventional vapour freezing (T1) and modified freezing protocol with an aluminium block (T2). After freezing-thawing, the progressive sperm motility, viability, HOS response and acrosome integrity were significantly (p ≤ 0.05) improved in treatment 2 compared to the control and treatment 1 groups. Along with this, the degree of oxidative stress (MDA production) was substantially lower in treatment groups (T1 and T2) compared to control group. The results highlight the promising effectiveness of the modified freezing method incorporating trehalose and glycerol as cryoprotectants and using an aluminium block. The significance of these findings lies in the potential application of this technique for freezing-thawing semen, particularly from bulls with poor freezability.